ADDITIVE MANUFACTURING FROM BIOMIMETIC APPROACH - Takács, Ágnes; Albert, Judit (Design of Machines and Structures, 2024)
During the past millions of years since the beginning of our world, nature has created structures that are resistant to the various effects of the environment. However, these natural structures are quite complicated, so their production and artificial reproducibility with the tools of traditional manufacturing technology is a very difficult task. However, even complex structures can be produced relatively easily with the help of additive manufacturing. Using topological optimization techniques, lattice structure models with excellent mechanical characteristics can be created, which can be easily manufactured by exploiting the advantages of additive manufacturing. Applying natural structures (biomimetic approach) during topological optimization and produce the solution by additive manufacturing, light and high-strength structural alternatives can be created, any further structural analyses can be done.